Membangun kompetensi lintas budaya melalui permainan adegan - Ratnasari, Dewi; Gantrisia, Kamelia; Cansrina, Genita (2021)
This research presents a theme that relates the concept of Scene Game and Cross-Cultural competence. Mastering foreign languages in this global era is an absolute absolute. In the mastery process, it is unavoidable that there is a very important stage, namely the process of understanding the accompanying culture of the foreign language being studied, because language carries its own culture. In fact, learning a foreign language is an intercultural meeting place that can lead to situations or circumstances that are full of cultural slices of two languages. The scene game or in German known as szenisches Spiel (Scheller; 2016) is a scene presentation with the theme of how a person behaves and interacts with other people or with society in dealing with situations that have the potential to cause conflict due to differences in behavior and viewpoints. This research is the result of observations of the 4th semester students of German Literature at Padjadjaran University in the Einführung in die Literaturwissenschaft course. In this course, the script for the musical drama "Linie 1" by Volker Ludwig (1986) is given, which is a literary work with a story and setting that is foreign to Indonesian students. Students discuss, interpret and reflect on the game scene. This research is the first step in a series of research with the theme of Game Scenes. Of course, further research is still needed to be able to conclude the relevance between scene game learning and the development and strengthening of cross-cultural competencies.